HUBUNGAN KUALITAS KEHIDUPAN KERJA PERAWAT DENGAN PERILAKU CARING PERAWAT DI RUMAH SAKIT PRISCILLA MEDICAL CENTER CILACAP - tarno; Tri Sumarni; Adiratna Siwi (Yakpermas Press, 2023)
The quality of work life is the right way to improve the quality of human resources because it will contribute to the success of the organization and have a positive impact on the organization. The quality of a good nurse's work life will have an impact on the quality of care for patients, where the quality of care describes the caring behavior of nurses towards patients. Caring behavior is very important in fulfilling patient satisfaction, because it is one of the indicators of service quality in hospitals. The purpose of this study was to analyze the relationship between the quality of work life of nurses and the caring behavior of nurses towards patients at PMC Cilacap Hospital. This research is a quantitative study with a cross sectional design. The sample of this study were all nurses in the inpatient room of PMC Cilacap Hospital, namely 45 nurses and 45 patients. The sampling method for nurses is saturated sampling (total sampling) and the sampling method for patients is to use a 1:1 ratio, ie the number of samples of nurses is equal to the number of samples of patients. The instrument used is the